Consumer acceptance of wearable technology devices :|A cross-cultural study in Turkey and Germany - Benderlioğlu, Bengi Meriç. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
With the rapid change in technology worldwide, products such as wearable technology devices tend to have an uprising trend that comes with wider variety nowadays. Consumers, however, are not necessarily adaptive in their nature and their perception is shaped by many factors. The aim of this research is to investigate the consumer acceptance of wearable technology devices. For this purpose, a research instrument was developed through which data was collected from German and Turkish university students. The study extends the widely used technology acceptance model with the introduction of new variables. The overall results provide validation to previous literature while introducing new factors for consumer acceptance of technology products, wearable technology devices and smartwatches, specifically. Importance of this research comes from the innovative and promising nature of the wearable technology devices concept, the lack of work on smartwatches in the literature as well as the cross-cultural nature of the study.
Keywords: Consumer behavior.; Wearable technology.